Successful Rehabilitation and Release of a Korean Water Deer (Hydropotes inermis argyropus) After a Femoral Head Ostectomy (FHO) - Sohwon Bae; Minjae Jo; Woojin Shin; Chea-Un Cho; Son-Il Pak; Sangjin Ahn (Animals)
A water deer (Hydropotes inermis argyropus) was rescued following a vehicle collision and presented with suspected hip injury. Radiographic examination confirmed coxofemoral luxation, and a femoral head ostectomy (FHO) was performed to restore functional mobility. Postoperatively, the water deer underwent intensive rehabilitation, including controlled movement and physical therapy, to enhance limb function. Following successful recovery, the water deer was equipped with a GPS collar and released into its natural habitat. GPS tracking data were collected to evaluate the water deer’s post-release adaptation and movement patterns. The Minimum Convex Polygon (MCP) method was used to determine the home range, showing an overall home range (MCP 95%) of 8.03 km2 and a core habitat (MCP 50%) of 6.967 km2. These results indicate a successful post-surgery outcome, with the water deer demonstrating mobility comparable to healthy individuals. This case demonstrates the clinical feasibility of an FHO in managing hip luxation in water deer and underscores the critical role of post-release monitoring in evaluating functional rehabilitation success in wildlife medicine. This study underscores the importance of integrating surgical intervention, structured rehabilitation, and post-release monitoring to ensure the successful reintroduction of injured wildlife. GPS tracking provides valuable insights into long-term adaptation and mobility, contributing to evidence-based conservation medicine.